Nurses' performance in changing the lifestyle of people with hypertension: narrative literature review (Research, Society and Development, 2021)
This study aimed to identify existing scientific productions on the role of nurses in changing the lifestyle of people with systemic arterial hypertension. This is a narrative review of the literature, developed during the month of October 2020, in the Latin American and Caribbean Literature in Health Sciences and in the Nursing Database, using as descriptors Hypertension, Nursing, Style and Health Education. The Boolean operator “AND” was used. The corpus of the study consisted of 05 articles. After the qualitative analysis, through the thematic analysis proposed by Minayo, the following thematic category emerged: The role of nurses in changing the lifestyle of people with systemic arterial hypertension. It was found through this study that the responsibility of nurses goes beyond being the mediator between the patient and hypertension, he is the professional capable of helping the person with hypertension to change their life, as their proximity and bond make with make this possible. Thus, issues related to lifestyle improvement, placed nurses as professionals close to the person, favoring their performance and the development of nursing care.